2014
DOI: 10.1021/jp503542y
|View full text |Cite
|
Sign up to set email alerts
|

Structural Transition of MnNb2O6 under Quasi-Hydrostatic Pressure

Abstract: High-pressure Raman scattering and X-ray diffraction studies on manganese niobate (MnNb 2 O 6 ) have been carried out in a diamond anvil cell at room temperature up to 41 GPa. A pressure-induced phase transition was observed at 12 GPa accompanied by the softening of two internal vibration modes ν 10 (B 2g ) and ν 8 (A g ). Disappearing of most Raman vibration peaks under high pressure reveals that the NbO 6 octahedra distort heavily through the transition; this is evidenced by the Xray diffraction results, but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 35 publications
2
28
1
Order By: Relevance
“…The (Mn,Fe)­(Nb,Ta) 2 O 6 family of compounds encompass two different solid solution series, named tantalite-columbite with orthorhombic structure and tapiolite-mossite with tetragonal structure, the compositional fields were presented in literature, of which the manganotantalite Mn­(Ta,Nb) 2 O 6 belongs to tantalite–columbite series. , They are the most important economic minerals containing base metals: Ta and Nb. In a stable state, manganotantalite shows a columbite-type structure that crystallizes in orthorhombic symmetry with space group of Pbcn , in which edge-sharing [AO 6 ] and [BO 6 ] octahedra chains run parallel along the c -axis. , There are other four synthetic polymorphs of MnTa 2 O 6 formed at different temperatures and pressures, which have trirutile, wolframite, wodginite, and modulated α-PbO 2 structures, respectively . Previous studies have focused on the properties of (Mn,Fe)­(Nb,Ta) 2 O 6 compounds at ambient and high-temperature conditions. It is reported that the changes in thermal expansion coefficients of unit cell parameters revealed anisotropic expansion behaviors of FeNb 2 O 6 , FeTa 2 O 6 , and MnTa 2 O 6 with temperature. ,, The thermodynamic research shows that FeNb 2 O 6 undergoes a phase transition from orthorhombic to tetragonal structure at 1630 K …”
Section: Introductionmentioning
confidence: 99%
“…The (Mn,Fe)­(Nb,Ta) 2 O 6 family of compounds encompass two different solid solution series, named tantalite-columbite with orthorhombic structure and tapiolite-mossite with tetragonal structure, the compositional fields were presented in literature, of which the manganotantalite Mn­(Ta,Nb) 2 O 6 belongs to tantalite–columbite series. , They are the most important economic minerals containing base metals: Ta and Nb. In a stable state, manganotantalite shows a columbite-type structure that crystallizes in orthorhombic symmetry with space group of Pbcn , in which edge-sharing [AO 6 ] and [BO 6 ] octahedra chains run parallel along the c -axis. , There are other four synthetic polymorphs of MnTa 2 O 6 formed at different temperatures and pressures, which have trirutile, wolframite, wodginite, and modulated α-PbO 2 structures, respectively . Previous studies have focused on the properties of (Mn,Fe)­(Nb,Ta) 2 O 6 compounds at ambient and high-temperature conditions. It is reported that the changes in thermal expansion coefficients of unit cell parameters revealed anisotropic expansion behaviors of FeNb 2 O 6 , FeTa 2 O 6 , and MnTa 2 O 6 with temperature. ,, The thermodynamic research shows that FeNb 2 O 6 undergoes a phase transition from orthorhombic to tetragonal structure at 1630 K …”
Section: Introductionmentioning
confidence: 99%
“…36 In addition, peaks are located below 400 cm À1 , corresponding to Fe-O or O-Nb-O bonds. 37,38 The surface chemical composition of FNO/rGO was characterized via XPS analyses. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…the two extreme compounds of the series NiNb 2−x V x O 6 are presented in the second and nineth columns of Table 6. As there are no theoretical studies on the normal coordinate analysis of the AB 2 O 6 compounds with the columbite structure when B = V, the identification of the symmetry of the modes presented in the first column of Table 6 was done by comparing our results with those of Raman studies performed in niobates of the AB 2 O 6 family already reported in the literature [20,21,23,24]. Raman spectra acquired for the complete series of NiNb 2−x V x O 6 samples at room temperature and pressure are presented together in Fig.…”
Section: Raman Spectroscopymentioning
confidence: 99%